2022
DOI: 10.1177/03091333221122292
|View full text |Cite
|
Sign up to set email alerts
|

Geodiversity inclusiveness in biodiversity assessment

Abstract: Biodiversity assessment is constitutive in establishing conservation priorities and outcomes, and geodiversity complements species richness as a surrogate in the absence of species data, improves statistical modelling and can facilitate prediction of species distribution and abundance. Yet, geodiversity is frequently excluded, and biodiversity prioritised in conservation endeavours such as ecosystem-based management. Therefore, combined geodiversity and biodiversity assessment approaches present practical bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 174 publications
(276 reference statements)
0
9
0
Order By: Relevance
“…This correlation between those partial indices of geodiversity and biodiversity is also detected between the geodiversity and biodiversity indices, which shows a potential dependence between both parameters. This was already explained by Parks and Mulligan (2010), Tukiainen et al (2016) or Crisp et al (2022). These authors postulated that geological factors (lithology, geomorphology, hydrology, pedology processes) condition the development of ecosystems and thus the colonization of new habitats.…”
Section: Discussionmentioning
confidence: 79%
“…This correlation between those partial indices of geodiversity and biodiversity is also detected between the geodiversity and biodiversity indices, which shows a potential dependence between both parameters. This was already explained by Parks and Mulligan (2010), Tukiainen et al (2016) or Crisp et al (2022). These authors postulated that geological factors (lithology, geomorphology, hydrology, pedology processes) condition the development of ecosystems and thus the colonization of new habitats.…”
Section: Discussionmentioning
confidence: 79%
“…Along with many researchers studying geodiversity and biodiversity (Boothroyd & McHenry, 2019;Crisp et al, 2023), we suggest that Gray's (2013) definition and terminology should be used consistently when bringing geodiversity into biodiversity research. We also recommend clearly communicating which components of geodiversity-all or some-from Gray's (2013) definition are included in biodiversity studies, as has been suggested in relation to ecosystem services (Fox et al, 2020).…”
Section: Con Clus Ions and Recommendationsmentioning
confidence: 94%
“…As many of the components included in the proposed geodiversity definition have been explored independently in ecology (e.g. hydrological diversity, Lawson et al, 2015;soil diversity, Stark et al, 2017;geological diversity, Antonelli et al, 2018), there is an opportunity to integrate and synthesize this research with existing research linking biodiversity and geodiversity (Crisp et al, 2023).…”
Section: Soluti On S and The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively simple approach for assessing the in‐stream geodiversity is to count the richness of the physical, hydrological and geomorphological features (Hjort & Luoto, 2010; Kärnä et al, 2018) in situ. Such approaches have been used in studies that attempt to explore the relationships between geodiversity and biodiversity (Heino et al, 2019; Toivanen et al, 2019; Tukiainen et al, 2019) and ultimately promote biodiversity conservation actions through the protection of the abiotic environment (Alahuhta et al, 2018; Crisp et al, 2022; Hjort et al, 2022). However, studies that investigate whether geodiversity metrics can be used as proxies for ecological quality of freshwater ecosystems are still lacking.…”
Section: Introductionmentioning
confidence: 99%